Estructura del macrobentos del estero de Jaltepeque, El Salvador - Molina Lara, Oscar Armando (1994)
A survey of the intertidal macrofauna of the Jaltepeque estuary, El Salvador, was conducted during December, 1990 (dry season) and July, 1991 (rainy season). A total of IS stationa were sampled along tite estuary, and IS sedimento samples (core area: 17.7 ana) were collected in each one, 10 a depth of IS ano Samples Were preserved in 10% fonnalin in sea water stained with Rose BengaL A SOO